TINJAUAN BENTUK PENGGUNAAN BAHAN/MATERIAL RUMAH(BUMI) ADAT KAMPUNG CIKONDANG, DESA LAMAJANG - Nani Sriwardani; Savitri Savitri (Narada : Jurnal Desain dan Seni, 2019)
This research at some part was an overview of previous studies which is standardization of the form of air circulation in Bumi Adat Kampung Cikondang, Village Lamajang and had been published in proceeding Sinden 2018.Bumi Adat Cikondang as object research in the Village Lamajang is selected since there is only one traditional house left in this village and it has become the site of cultural heritage. Architecture of Bumi Adat is built around the 16th century, and currently is a part of tourism in West Java. The traditional house lost during the fire in 1942, and was not be built again because of local restriction believes as well as limited building material in the sacred woods. Bumi Adat is in total use of natural material, such as bamboo, wood and palm fibers.The use of natural materials for the whole building create the work that have been able to survive until now.Methods used in this research is a qualitative methodology with descriptive analysis supported by observation and study in the field and study in literature review.The aimed at this research is to describing the shape of the use of natural material until become traditional building.